BOHDAN HAVRYLYSHYN’S SUPPORT TO THE DEVELOPMENT OF INTERNATIONAL RELATIONS OF UKRAINE (Південний архів (історичні науки), 2023)
The research purpose is find out how the representative of the Ukrainian diaspora Bohdan Hawrylyshyn contributed to the establishment and development of international cooperation of the Ukrainian state. The methodological foundation of the research became methods of analysis, synthesis, principles of historicism and objectivity. The main results of the study. It was during a certain period of time that significant geopolitical changes took place in the territory of Central and Eastern Europe due to the collapse of the Union of Soviet Socialist Republics and the liquidation of the Warsaw Pact Organization. These events led to the declaration of Ukrainian independence and the establishment of international cooperation, with the aim of full-fledged entry into the group of free countries of the world. As a result of these processes, it was extremely important to establish personal interpersonal contacts with leading world leaders and figures. In this regard, Bohdan Dmytrovych Hawrylyshyn came to the aid of Ukrainian statehood and diplomacy. Conclusions. In his memoirs and interviews given by him at different times, Bohdan Gavrylyshyn shared the impressions he saw and the things he did with his participation, which cannot be found in other types of historical sources. Improving the efficiency of the Ukrainian people became one of the leading themes of both his memories and activities. Establishing international contacts is also a component of efficiency. As a result of the conducted research, it was established that he was an adviser to President Leonid Kravchuk and three prime ministers, helping them to establish important global contacts. The scientist introduced the Ukrainian elite to the World Economic Forum in Davos, which significantly expanded their contacts and opportunities for the development of Ukraine. Disillusioned with Ukrainian politicians, the scientist founded the Bohdan Gavrylyshyn Charitable Foundation in 2010, the purpose of which is to train a significant group of young Ukrainians who would learn from their own experience how advanced European states function and be able to change Ukraine for the better.
Keywords: Bohdan Hawrylyshyn, diaspora, independent Ukraine, adviser to the president, institutions, international relations, charity fund